The simplification of public administration: A managerial perspective - Guido Modugno; Michele Bertoni; Bruno De Rosa (Naše gospodarstvo / Our Economy, 2022)
The paper addresses the issue of complexity in the administrative processes of public institutions: in particular, accounting routines and processes are examined. Back-office activities, although having a mere supporting role in the delivery of public services, absorb a relevant part of the resources of public institutions. The aim of the paper is to analyse the factors that contribute to the enhancement of complexity of these activities. The paper is based on an in-depth analysis of two Italian public organisations: a university and an ASP (agency for services to persons). Italy is an interesting context since simplification policies have been adopted in the country at central government level and in specific sectors of public administration, however, at the institutional level, simplification initiatives depend on the initiative of the single organisation. The cases described in this paper show that complexity stems from the need for inspectory controls (which is typical of the law) as well as from the volume of information requested (which is typical of management studies) for different stakeholders and at different, yet correlated, levels. The paper suggests that public management scholars have the opportunity and the burden of a contribution in this field.
Keywords: M41; M48; 330; simplification; support activities; processes; public administration; stakeholders